The drowned boy - Fossum, Karin, 1954- (Fossum, Karin, 1954- Inspector Sejer mystery., 2015)
"A new addition to the captivating Inspector Sejer series, the first since The Caller, from Norway's finest crime writer Carmen and Nicolai failed to resuscitate their son, Tommy, after finding him floating in their backyard pond. When Inspector Skarre arrives on the scene, Carmen reports that Tommy, a healthy toddler with Down syndrome, wandered into the garden while Nicolai was working in the basement and she was cleaning the house. Skarre senses something is off with Carmen's story and consults his trusted colleague, the famed Inspector Sejer. An autopsy reveals Tommy's lungs to be full of soap. When Sejer and Skarre revisit the couple, Carmen, an epileptic, changes her story, confessing that she'd been knocked unconscious by a seizure while bathing Tommy. When she came to, she found him drowned in the tub and, horrified and frightened, threw him into the pond. But Skarre and Sejer's doubt is not appeased and the case is reopened. What more could Carmen be hiding? And what lengths will she take to cover her guilt? As Carmen's own family starts to doubt her, Skarre and Sejer work to find the truth."--